Globalization Challenges to State Sovereignty in Philosophical Dimension - Yunus, Nur Rohim (BULETIN ADALAH, 2024)
This essay discusses the challenges faced by state sovereignty in the era of globalisation by integrating the perspective of political philosophy. Globalisation, which increases the interconnectedness of states, has a significant impact on the concept of state sovereignty, especially in economic, cultural, and political aspects. In the financial field, globalisation limits state domestic policies through global market pressures and international agreements. Contemporary political philosophy includes the debate between maintaining state sovereignty and global responsibilities, such as international justice and cross-border solidarity. Cultural globalisation threatens national identity, where global values often replace local cultures. States must formulate wise policies to maintain national autonomy while adapting to global changes. In this context, political philosophy offers a normative framework emphasising the balance between domestic interests and international responsibilities, to realise a more just and harmonious world.